Piracy, Price Discrimination, and Development: The Software Sector in Eastern Europe and Other Emerging Markets - Cosovanu, Catalin (Science and Technology Law Review, 2004)
The strengthening of intellectual property regimes in Eastern Europe and other emerging markets has failed to deliver on the much-touted promises of increasing high-technology foreign investment and faster development of homegrown information-intensive industrial sectors, especially with respect to the software industry. Considering the economics of developing and marketing software products, local programmers have little to gain from stronger copyright protection in their domestic markets, and this situation is not likely to change soon. The technological level of foreign investment and its global pattern (advanced research and development in the core, unsophisticated and low margin work in the periphery) is also unaffected by the local level of copyright protection. At the same time, piracy has turned out to be a necessary evil for the diffusion of software that is legally priced beyond the reach of most local users. Price discrimination could have provided a solution for this conundrum, but there are important economic and political factors that support the status quo, although the much-feared parallel imports are less of a problem than expected. Nevertheless, there are significant technological and cultural developments that should make the actors involved less comfortable about the status quo. These problems clearly require more innovative thinking. Open source software is likely to be a significant part of the answer, but the implementation of this solution will require serious efforts to change the approach of governments in developing countries and the international organizations involved in development assistance.